A meta-analysis of willingness to pay for local beef - Stutzman, Amy (My University, 2020)
Over the past few decades, consumer demand for fresh locally produced foods has been increasing. This demand is most evident in the increasing number of farmers markets that brought farmers and their fresh locally produced produce closer to local consumers across the country. Between 2002 and 2012, US farm operations with food sales directly to consumers increased from 5.5 % to 6.9%. The 2007 Census of Agriculture reported direct-to-consumer sales revenue of $1.2 billion, a significant increase from $551 million reported a decade earlier. As the direct-to-consumer market for farmers expanded, researchers’ interest in the factors influencing consumers’ willingness to pay also increased. Numerous studies were conducted between the early 1990s and the mid-2000s about this topic. They covered numerous products, locations, and consumers segments. It is difficult to make sense of the results given their diversity and breadth. This research attempts to bring some clarity to the results from the various studies by focusing on a single product in the US: locally produced ground beef. The study used five qualifying studies in the US and a meta-analysis approach to estimate the factors influencing consumers’ willingness to pay given their characteristics. The results from this study bring the diverse results from the five different studies together to provide a comprehensive insight into the characteristics of consumers that determine their willingness to pay. These results would be helpful to beef farmers and their supply chain partners who are seeking to enhance their value extraction by working in the local direct-to-consumer market. The results show that the average willingness to pay for local ground beef was about $1.28 per pound above commodity ground beef, with a standard deviation of $0.04 per pound. There was statistical difference between the premium female and male consumers were willing to pay for fresh local ground beef. However, the difference in the premiums those with bachelor’s degree or higher and those without was statistically significant at the 1% level. Similarly, the difference between the premiums those with incomes above $75,000 and those with incomes below $75,000 were willing to pay was statistically significant at the 5% level. Race did not influence the premiums consumers were willing to pay. Consumers in the Midwest, the Northeast and the South were all willing to pay more than consumers at the national level, and the differences between their premiums were statistically significant at the 1% level. The foregoing would suggest that farmers interested in producing fresh local ground beef for direct to consumer marketing should segment the market to target those with higher education and incomes. Agricultural regions of the country present more competition, and it may be more difficult for farmers in these regions to extract higher premiums that farmers in non-agricultural regions.
Keywords: Local beef; willingness to pay; direct-to-consumer market; meta-analysis